Salvage Radiation Therapy for Patients With Relapsing Glioblastoma Multiforme and the Role of Slow Fractionation - Ciernik, I. Frank; Gager, Yann; Renner, Christof; Spieker, Sybille; Arndt, Nicole; Neumann, Karsten (Frontiers in Oncology, 2020)
Background: Salvage radiation therapy (SRT) can be offered to patients with relapsing glioblastoma multiforme (GBM). Here we report our experience with a schedule extending the treatment time of SRT with the aim to prolong the cytotoxic effect of ionizing radiation while minimizing the cytotoxic hazards for the surrounding brain. Methods and Patients: From 2009 until 2017, 124 of 218 patients received radical resection, adjuvant chemo-radiation with photons and temozolomide (TMZ) followed by adjuvant TMZ. Re-irradiation was performed in 26 patients due to local relapse. Treatment schedules varied from hypofractionation given within 5 days to extend re-irradiation exceeding 25 days. Survival and molecular markers were assessed. Results: The median survival of the 124 patients treated in tri-modal therapy was 12 months (9-14.5) and 19.2 months (14.9-24.6) for the 26 patients retreated with SRT (p=0.038). Patients who received daily fractions of 1,6 to 1,65 Gy to a total dose of >40 Gy had a median survival time of 24,6 months compared to patients treated with higher daily doses or a total dose of <40 Gy (p= 0.039), consistent with the observation that patients treated with 21-28 fractions had a median survival of 21,9 months compared to 15,8 months of patients who received 5-20 fractions (p=.0.05). Patients with Ki-67 expression of >30% seemed to perform better than patients with expression levels of ≤20% (p=0.03). MGMT methylations status, TERT promoter and ATRX mutations, overexpression of p53, p16, PD-L1, and EGFR were not prognostic. Conclusions: Re-irradiation of relapsing GBM is a highly valid treatment option. Our observation challenges hypofractionated stereotactic radiotherapy for retreatment and controlled trials on the fractionation dose for SRT are needed. Robust predictive molecular markers could be beneficial in the selection of patients for SRT.